Educational application and games for specific skills development - Özmen, Erhan (IGI Global, 2025)
This chapter addresses the transformative role of educational apps and games in the development of cognitive, social, emotional, motor and technological skills. Digitalised education promotes 21st century competences such as problem solving, critical thinking and collaboration, while increasing interactivity, motivation and individualised learning. Applications such as Duolingo and Kahoot make learning interactive and fun with reward and challenge systems. Tools such as virtual reality contribute to the development of motor skills, while platforms such as Tynker support cognitive growth. Social-emotional learning applications such as ClassDojo develop empathy and self-regulation skills. The chapter highlights the theoretical underpinnings of these innovations, such as constructivism and motivation theories, while also highlighting challenges such as the need for pedagogical alignment and cultural adaptation. It also sheds light on the potential of educational apps and games to create engaging, motivating learning environments. © 2025, IGI Global Scientific Publishing. All rights reserved.